THE ROLES OF BHAYANGKARA OF TRUSTEES OF SECURITY AND PUBLIC ORDER (BHABINKAMTIBMAS) OF THE POLICE OF REPUBLIC OF INDONESIA (POLRI) IN IMPLEMENTATION OF RESTORATIVE JUSTICE AGAINST CRIMINAL OF PRESECUTION IN THE LAW OF THE NORTH BENGKULU POLICE - Yosril Radiansyah; Antory Royan Adyan; Hamzah Hatrik (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
This study raises issues related to the roles of Bhabinkamtibmas and the constraints of Bhabinkamtibmas in implementing restorative justice against criminal acts of persecution in the North Bengkulu Police. This study aims to find out and analyze what the roles and constraints of Bhabinkamtibmas in implementing the process of restorative justice against criminal acts are. This research is an empirical legal research type from the facts that exist ina society, legal entity or government agency. The results of this study indicate that the existence of Bhabinkamtibmas has helped many Police institutions especially North Bengkulu Resort Police starting from the early detection of criminal acts (pre-emptive functions), the process of preventing criminal acts (preventive functions) and the process of problem solving and law enforcement (repressive functions) one of its role is as a mediator and facilitator inthe process of restorative justice. The constraints or obstacles of Bhabinkamtibmas in carrying out their roles from the internal of the National Police and the personnel of Bhabinkamtibmas itself are related to knowledge, skills and ethics as well as external constraints such as the lack of a legal culture or response from the public and the absence of positive laws governing. The results of this study suggest that it needs legal reforms that accommodate the process of restorative justice in order to improve the legal culture and effectiveness of criminal law enforcement in Indonesia.